0.9(9x+6)=2.5-(x-3)

Simple and best practice solution for 0.9(9x+6)=2.5-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9(9x+6)=2.5-(x-3) equation:


Simplifying
0.9(9x + 6) = 2.5 + -1(x + -3)

Reorder the terms:
0.9(6 + 9x) = 2.5 + -1(x + -3)
(6 * 0.9 + 9x * 0.9) = 2.5 + -1(x + -3)
(5.4 + 8.1x) = 2.5 + -1(x + -3)

Reorder the terms:
5.4 + 8.1x = 2.5 + -1(-3 + x)
5.4 + 8.1x = 2.5 + (-3 * -1 + x * -1)
5.4 + 8.1x = 2.5 + (3 + -1x)

Combine like terms: 2.5 + 3 = 5.5
5.4 + 8.1x = 5.5 + -1x

Solving
5.4 + 8.1x = 5.5 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
5.4 + 8.1x + x = 5.5 + -1x + x

Combine like terms: 8.1x + x = 9.1x
5.4 + 9.1x = 5.5 + -1x + x

Combine like terms: -1x + x = 0
5.4 + 9.1x = 5.5 + 0
5.4 + 9.1x = 5.5

Add '-5.4' to each side of the equation.
5.4 + -5.4 + 9.1x = 5.5 + -5.4

Combine like terms: 5.4 + -5.4 = 0.0
0.0 + 9.1x = 5.5 + -5.4
9.1x = 5.5 + -5.4

Combine like terms: 5.5 + -5.4 = 0.1
9.1x = 0.1

Divide each side by '9.1'.
x = 0.01098901099

Simplifying
x = 0.01098901099

See similar equations:

| -3n-1/2(-4-4n)=7 | | 283=3.14(5)l+(3.14)25 | | 5+(-3w+-12)=w+-7 | | -12.2y-8.68=-11.34-13.6y | | 2e^6= | | 3(3x-2)=7(x+6)+7 | | 1/2x-5=3x-10 | | 9x+6y=150 | | 283=3.14(5)l+25 | | 2(5x-3)-1=13 | | 6v+6=4v+2(v+3) | | 3.1-0.2a=1.5 | | m+m+5+m+8=84 | | 5-2p=7 | | -7.26+18p=6p-2.22+12.3p | | 3x+4y=75 | | 4x-48=36 | | 25.50x=12.50 | | -1=c-6 | | 6x+(3x-2)=14 | | -7v-5=-5v-9 | | x^2-7/3x-2/3 | | X+-5=6 | | -20+2x=30 | | 184=6y+4 | | -2n(9-10n)= | | 25.50=13.50 | | 8/3=32/x | | 6.2h+51.4h=4.8h+5 | | 6x+10=-7x-3 | | -2=a+6 | | 12(1)-4y=16 |

Equations solver categories